Soybean miR172c Targets the Repressive AP2 Transcription Factor NNC1 to Activate ENOD40 Expression and Regulate Nodule Initiation . Issue 12 (30th December 2014) - Wang, Youning; Wang, Lixiang; Zou, Yanmin; Chen, Liang; Cai, Zhaoming; Zhang, Senlei; Zhao, Fang; Tian, Yinping; Jiang, Qiong; Ferguson, Brett J.; Gresshoff, Peter M.; Li, Xia
Abstract : Induction of miR172c in response to rhizobial inoculation activates ENOD40 expression and nodule formation by repressing an AP2/ERF transcription factor, called NNC1, that acts to inhibit ENOD40 expression. Abstract: MicroRNAs are noncoding RNAs that act as master regulators to modulate various biological processes by posttranscriptionally repressing their target genes. Repression of their target mRNA(s) can modulate signaling cascades and subsequent cellular events. Recently, a role for miR172 in soybean ( Glycine max ) nodulation has been described; however, the molecular mechanism through which miR172 acts to regulate nodulation has yet to be explored. Here, we demonstrate that soybean miR172c modulates both rhizobium infection and nodule organogenesis. miR172c was induced in soybean roots inoculated with either compatible Bradyrhizobium japonicum or lipooligosaccharide Nod factor and was highly upregulated during nodule development. Reduced activity and overexpression of miR172c caused dramatic changes in nodule initiation and nodule number. We show that soybean miR172c regulates nodule formation by repressing its target gene, Nodule Number Control1, which encodes a protein that directly targets the promoter of the early nodulin gene, ENOD40 . Interestingly, transcriptional levels of miR172c were regulated by both Nod Factor Receptor1α/5α -mediated activation and by autoregulation of nodulation-mediated inhibition. Thus, we established a direct link between miR172c and the Nod factor signaling pathway in addition to adding a new layer to the precise nodulation regulation mechanism of soybean.